Indonesia’s FTF Returnee Framework: Densus 88, RAN PE, and Reintegration Challenges - nova, reeza andi; Pratidina, Fani Aisyah (Jurnal Ilmu Kepolisian, 2026)
This study employs a Qualitative Document Analysis (QDA) method to evaluate Indonesia’s repatriation framework. Data were purposively selected from three primary sources: (1) Statutory documents, including Presidential Decree No. 7/2021 (RAN PE) and Law No. 5/2018; (2) Official institutional reports from Densus 88 AT and BNPT regarding FTF management; and (3) Secondary academic literature from 2019–2024 to ensure contemporary relevance. The analysis followed a thematic approach: documents were first coded to identify the operational mandates of Densus 88, then triangulated against the pillars of RAN PE to identify implementation gaps. Finally, findings were derived through deductive reasoning, mapping these legal mandates against the practical challenges of reintegration in the field. The findings indicate that while Densus 88 plays a crucial role in early detection and neutralizing immediate tactical threats, the implementation of RAN PE faces hurdles in inter-agency coordination and the balance between security-centric measures and humanistic reintegration. The research highlights the necessity of a "unity of effort" between Densus 88 and social-sector stakeholders to prevent recidivism. Ultimately, this study concludes that the effectiveness of handling returning FTFs depends on the seamless integration of Densus 88’s specialized intelligence into the broader socio-ideological rehabilitation programs mandated by the RAN PE, ensuring that returnees are neutralized ideologically as well as tactically.